Arterial and microvascular supply of cerebral hemispheres in the nude mouse revealed using corrosion casting and scanning electron microscopy - Sangiorgi, Simone (J Anat, 2018)
Morphological analyses of cerebral vascularization are not only important for the characterization of the anatomical and physiological relationships between vascular and nervous tissue, but also required to understand structural modifications that occur in many pathological conditions affecting the brain. The aim of this study was to generate a three‐dimensional vascular map of the cerebral hemispheres in the nude mouse brain, a widely used animal model for studying tumour biology. We used the corrosion casting (CC) technique to isolate blood vessels from 30 nude mouse brains. All casts were analysed using scanning electron microscopy (SEM), which generated quantitative data regarding vessel length and diameter as well as inter‐vascular and inter‐branching distances. We identified three different topographical regions: (i) the cortical region, characterized by a superficial wide sheet of vessels giving rise to terminal perforant vessels that penetrate the grey matter; (ii) the inner part of the grey matter, in which dense capillary nets form many flake‐like structures extending towards the grey–white matter boundary, where perforant vessels finally change direction and form a well‐defined vascular sheet; and (iii) the white matter layer, characterized by a more disorganized vascular architecture. In this study, we demonstrate the accuracy of the CC‐SEM method in revealing the 3D‐topographical organization of the vascular network of the normal nude mouse brain. These baseline data will serve as a reference for future anatomical investigations of pathological alterations, such as tumour infiltrations, using the nude mouse model.